Status Kelembagaan RTRI dalam Perspektif Hukum - Denico Doly (Jurnal Komunikasi, 2013)
Public Service Broadcaster (LPP) in Indonesia is organized by Radio Republik Indonesia (RRI) and Televisi Republik Indonesia (TVRI). The main problem that these institutions have to face is the Indonesian state institution system does not recognize the status of LPP. This situation leads to other problems that hinder the development of LPP RRI and LPP TVRI. The merger between LPP RRI and LPP TVRI to become RTRI is one of the efforts in solving the problems. The status of RTRI as an independent public service broadcasting should be mentioned clearly in the regulation. Therefore, RTRI as a state institution will be independent and serves public demands on public broadcasting.